Tracking strategy for photovoltaic solar systems in high latitudes. (October 2015) - Quesada, Guillermo; Guillon, Laura; Rousse, Daniel R.; Mehrtash, Mostafa; Dutil, Yvan; Paradis, Pierre-Luc
Highlights: In cloudy conditions tracking the sun is ineffective. A methodology to estimate a theoretical threshold for solar tracking was developed. A tracking strategy to maximize electricity production was proposed. Abstract: Several studies show that from about 20% to 50% more solar energy can be recovered by using photovoltaic systems that track the sun rather than systems set at a fixed angle. For overcast or cloudy days, recent studies propose the use of a set position in which each photovoltaic panel faces toward the zenith (horizontal position). Compared to a panel that follows the sun's path, this approach claims that a horizontal panel increases the amount of solar radiation captured and subsequently the quantity of electricity produced. The present work assesses a solar tracking photovoltaic panel hourly and seasonally in high latitudes. A theoretical method based on an isotropic sky model was formulated, implemented, and used in a case study analysis of a grid-connected photovoltaic system in Montreal, Canada. The results obtained, based on the definition of a critical hourly global solar radiation, were validated numerically and experimentally. The study confirmed that a zenith-set sun tracking strategy for overcast or mostly cloudy days in summer is not advantageous.